Enabling Cybersecurity Mechanisms in a SmartPatch-Based Emergency Response System - Kostoska, Magdalena; Trajkovikj, Vladimir; Koteska, Bojana; Ackovska, Nevena; Fedor Lehocki; Madevska Bogdanova, Ana (IEEE, 2023)
This paper elaborates on the cybersecurity challenges of a healthcare system that includes a chest-patch (SmartPatch) sensor, used for the process management of massive victims’ events. Integrating biosensors into emergency communication strategies requires mechanisms for achieving trustful communication.A use case of usage Bluetooth LE communication between SmartPatch and other device is presented in the paper, and presents the security challenges and potential solutions.
Keywords: Emergency Response System; Smart Patch; Cybersecurity Mechanisms